Intra-cyclic analysis of the breastroke swimming technique using an inertial measurement unit - Engel, A.; Ploigt, R.; Mattes, K.; Schaffert, N. (Journal of Sport and Human Performance, 2021)
Inertial measurement units (IMU) are becoming increasingly relevant to motion analysis among scientists as they become more accessible and less annoying for athletes. They are also a promising alternative to time-consuming video analysis. Current research in swimming focuses on the analysis of global parameters for the four competing strokes, such as stroke frequency, number of cycles and timing, and fails to look at intra-cyclical parameters that are known to have an important impact on overall performance. The aim of this study was to analyze the intra-cyclical breaststroke patterns of 10 athletes of different performance levels who swam 100 m each with medium effort and performed a total of 357 swimming strokes. The data obtained were linked to the video to extract previously described key positions and and their corresponding data points in order to explore similarities in the data structure between all athletes and for different performance levels. The results were pretty clear, that regardless of the athlete`s level, certain global patterns in the data structure exist, which allow for an automatic intra-cyclic analysis of the breaststroke. This enables sport scientists to detect mistakes in movement performance, objectify the technical analysis and help coaches improve their training load and adapt it to the fatigue and specific needs of each athlete.